Rekonstruksi Materi Ilmu Pendidikan Islam di Era Disrupsi: Tinjauan Epistemologis dan Integrasi Kurikulum - Iin Himatul Islamiah; M. Asep Rahmatullah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Islamic Educational Science (IES) faces critical dualism in knowledge frameworks and profound moral disruption in the contemporary era. This study comprehensively examines fundamental Islamic educational materials, spanning from crucial epistemological foundations, basic terminology deconstructions, overarching macro objectives, complex systemic components, to innovative non-dichotomous curriculum transformation models. By applying a critical literature analysis, the results reveal that restructuring the comprehensive IES curriculum fundamentally requires the organic integration of qauliyah verses (divine revelation) and kauniyah verses (empirical science) under a unified framework of Tawhid. Furthermore, this article clearly delineates how traditional prophetic teaching methodologies, including uswah hasanah (exemplary character), mau'izhah (compassionate advice), and hiwar (interactive dialogue), can be effectively revitalized into advanced 21st-century learning models. This optimization aims to produce Insan Kamil (the complete human) who are fully prepared to navigate modern digital technological shifts without losing their vital spiritual roots or cultural identity. The direct implication of this academic study provides a robust conceptual framework for contemporary Islamic educational institutions to design, develop, and implement an integrated curriculum that bridges sacred and profane sciences effectively.